(untitled) (Research, Society and Development, 2024)
This article is part of research for a Doctoral Thesis in Science Teaching at the Federal University of Mato Grosso do Sul – UFMS. The objective of this article is to present part of the doctoral research aimed at understanding the experience of investigative practices in Teacher Training at a public Higher Education Institution in the State of Piauí. It is the result of a qualitative study that carried out a Document Analysis in the Pedagogical Course Project, and application of questionnaires with the course coordinator, teacher trainer in Supervised Internship and four undergraduate students, on the theme of Investigative Teaching in teacher training. The data was analyzed using Eni Orlandi’s Discourse Analysis. The EI experience in the institution is occurring in an interesting way, but it is limited to the intentional action of some trainers. EI is not included in the course curriculum. This teaching action is a product of the influence of the Continuing Training of some of the institution’s trainers in the Professional Master’s Degree in Biology Teaching - PROFBIO. We consider the influence of PROFBIO on the institution to be very positive on the experience of EI during the training of undergraduate students.